In Situ Dilatometry Measurements of Deformation of Microporous Carbon Induced by Temperature and Carbon Dioxide Adsorption under High Pressures - Andrey Shkolin; Il’ya Men’shchikov; Elena Khozina; Anatolii Fomkin (Colloids and Interfaces, 2023)
Adsorption-based carbon dioxide capture, utilization, and storage technologies aim to mitigate the accumulation of anthropogenic greenhouse gases that cause climate change. It is assumed that porous carbons as adsorbents are able to demonstrate the effectiveness of these technologies over a wide range of temperatures and pressures. The present study aimed to investigate the temperature-induced changes in the dimensions of the microporous carbon adsorbent Sorbonorit 4, as well as the carbon dioxide adsorption, by using in situ dilatometry. The nonmonotonic changes in the dimensions of Sorbonorit 4 under vacuum were found with increasing temperature from 213 to 573 K. At T > 300 K, the thermal linear expansion coefficient of Sorbonorit 4 exceeded that of a graphite crystal, reaching 5 × 10−5 K at 573 K. The CO2 adsorption onto Sorbonorit 4 gave rise to its contraction at low temperatures and pressures or to its expansion at high temperatures over the entire pressure range. An inversion of the temperature dependence of the adsorption-induced deformation (AID) of Sorbonorit-4 was observed. The AID of Sorbonorit-4 and differential isosteric heat of CO2 adsorption plotted as a function of carbon dioxide uptake varied within the same intervals of adsorption values, reflecting the changes in the state of adsorbed molecules caused by contributions from adsorbate–adsorbent and adsorbate–adsorbate interactions. A simple model of nanoporous carbon adsorbents as randomly oriented nanocrystallites interconnected by a disordered carbon phase is proposed to represent the adsorption- and temperature-induced deformation of nanocrystallites with the macroscopic deformation of the adsorbent granules.